Mechanisms and Regulation of Extracellular DNA Release and Its Biological Roles in Microbial Communities - Ibáñez de Aldecoa, Alejandra L.; Zafra, Olga; González-Pastor, José E. (Frontiers in Microbiology, 2017)
The capacity to release genetic material into the extracellular medium has been reported in cultures of numerous species of bacteria, archaea and fungi, and also in the context of multicellular microbial communities such as biofilms. Moreover, extracellular DNA (eDNA) of microbial origin is widespread in natural aquatic and terrestrial environments. Different specific mechanisms are involved in eDNA release, such as autolysis and active secretion, as well as through its association with membrane vesicles. It is noteworthy that in microorganisms, in which DNA release has been studied in detail, the production of eDNA is coordinated by the population when it reaches a certain cell density, and is induced in a subpopulation in response to the accumulation of quorum sensing signals. Interestingly, in several bacteria there is also a relationship between eDNA release and the development of natural competence (the ability to take up DNA from the environment), which is also controlled by quorum sensing. Then, what is the biological function of eDNA? A common biological role has not been proposed, since different functions have been reported depending on the microorganism. However, it seems to be important in biofilm formation, can be used as a nutrient source, and could be involved in DNA damage repair and gene transfer. This review covers several aspects of eDNA research: i) its occurrence and distribution in natural environments, ii) the mechanisms and regulation of its release in cultured microorganisms, and iii) its biological roles. In addition, we propose that eDNA release could be considered a social behavior, based on its quorum sensing-dependent regulation and on the described functions of eDNA in the context of microbial communities.